PRESERVASI NASKAH LONTAR KUNO DI MUSEUM GEDONG KIRTYA SINGARAJA BALI - putrayana, i putu (ACARYA PUSTAKA, 2018)
PRESERVASI NASKAH LONTAR KUNODI MUSEUM GEDONG KIRTYA SINGARAJA BALIOleh:I Putu Putra Yana WardanaABSTRACTThis study aimed at describing the activity of preserving ancient lontar texts, findingout the physical condition of the lontar text, finding out the damaging factors, theenvironmental control done and especially the extent the preservation process of mediumtransfer from the physical form to the digital one has been done by people who are incharge in Gedong Kirtya museum management in keeping the existence of the lontar. Thisstudy used a qualitative approach. The study used observation, interview, and documentanalysis as the methods of collecting the data. Based on the facts above it can be said thatGedong Kirtya has made an effort to preserve the texts which are stored in it. Thepreservation effort made has been in the form of closely following the condition in themaking , caring and storing the texts being managed.Keywords: preservation, text, museum, Gedong Kirtya.PENDAHULUAN